Human rights in thick and thin societies : universality without uniformity / Seth D. Kaplan. - Kaplan, Seth D., 1966- (Cambridge University Press, 2018)
Socio-centric societies have vibrant - albeit different - concepts of human flourishing than is typical in the individualistic West. These concepts influence the promotion of human rights, both in domestic contexts with religious minorities and in international contexts where Western ideals may clash with local norms. Human Rights in Thick and Thin Societies uncovers the original intentions of the drafters of the Universal Declaration of Human Rights, finds inspiration from early leaders in the field like Eleanor Roosevelt, and examines the implications of recent advances in cultural psychology for understanding difference. The case studies included illustrate the need to vary the application of human rights in differing cultural environments, and the book suggests a new framework: a flexible universalism that returns to basics - focusing on the great evils of the human condition. This approach will help the human rights movement succeed in a multipolar era.